OFF-BALANCE PHOSPHATE RAW MATERIALS OF THE ZHANATAS DEPOSIT: COMPREHENSIVE STUDY OF COMPOSITION AND STRUCTURE: ЖАҢАТАС КЕН ОРНЫНЫҢ БАЛАНСТАН ТЫС ФОСФАТ ШИКІЗАТЫ: ҚҰРАМЫ МЕН ҚҰРЫЛЫМЫН КЕШЕНДІ ЗЕРТТЕУ - Shaimerdenova, Guldana; Zhantasov Kurmanbek Tazhmakhanbetovich; Dormeshkin Oleg Borisovich; Mussirepova Elmira Berikbaikyzy; Tastanbekova Bayan Omirzahovna (Academic Scientific Journal of Chemistry, 2021)
The article presents the results of physicochemical studies of the composition and structure of off-balance raw materials from the Zhanatas deposit, located in the phosphorite-containing depression Karatau (South Kazakhstan). For the study, modern instrumental methods of physical and chemical analysis were used. The elemental-material composition is determined by the method of chemical analysis in accordance with the rules of regulatory documents and standards. The results of these studies are of practical importance for their further processing into phosphorus-containing products. Mineral fertilizers, including diammonium phosphate and off-balance phosphate raw materials in the agroindustrial sector of the economy play a key role in increasing the yield and quality of agricultural crops. Therefore, given the export orientation of the products of the phosphorus industry, it cannot be considered outside of macroeconomics, information is provided on the mineral petrographic analysis and the chemistry of the process of obtaining DAP based on the results of X-ray phase analysis obtained by IRS and on a scanning electron microscope. Filming was carried out on a D8 Advance (Bruker) apparatus, Cu-Kа, tube voltage 40 kV, current 40 mA. The processing of the obtained data of diffraction patterns and the calculation of interplanar distances were carried out using the EVA software. Sample decoding and phase search were carried out using the Search / match program using the PDF-2 powder diffractometric data base (ICDD).